Dynamic modulus of Western Australia asphalt wearing course - Wibisono, G.; Nikraz, Hamid (2014)
In the new AASHTO Mechanistic-Empirical Pavement Design Guide (MEPDG), the dynamic modulus |E*| test has been selected to assess the performance of asphalt concretes. The type of test, which relates asphalt mixtures modulus to temperature and time rate of loading, is never used in Western Australia. This paper presents a study on the dynamic modulus of typical Western Australia asphalt mixtures. Five mixtures with 10mm nominal sizes and two types of bitumen classes, i.e. C170 (Pen 60/80) and C320 (Pen 40/60) comply with Main Road Western Australia (MRWA) Specification were used in the research. Mixing and compacting process were carried out according to Austroads methods. The specimens were compacted using a gyratory compactor to achieve 5±0.5% target air void. Testing was performed at four temperatures (4, 20, 40 and 55°C) and six frequencies (25, 10, 5, 1, 0.5, 0.1 and 0.05 Hz). Dynamic modulus and phase angle master curves were generated from the results. The master curves were compared to the curves from Witczak’s predictive equation. From this preliminary study, it was found that the measured values correlated well with the predictive equation except at high temperatures or low frequencies.